Urban Invasive Plants in Brunei Darussalam – Distribution, Impact, and Management: A Review - Aidi Wan Mohammad; Zulkarnaen Rizmoon Nurul (BIO Web of Conferences)
Urbanization significantly changes landscapes, making urban areas highly susceptible to invasive plant species. This study examines Brunei Darussalam, where rapid urban development and rich biodiversity present unique challenges by systematically surveying invasive plant species in urban Brunei. The research identified two invasive plant species easily recognized by the public, such as Acacia mangium and Dillenia suffruticosa. The findings reveal that Acacia mangium has a widespread impact, outcompeting native flora and disrupting habitat structures due to its rapid growth and adaptability. Although Dillenia suffruticosa is culturally significant and ecologically important, it also exhibits invasive tendencies that could threaten local biodiversity. The study highlights the urgent need for targeted management strategies to control these species and safeguard native ecosystems. Effective management is crucial to preserve ecological balance and biodiversity amidst ongoing urban expansion. This research provides essential insights into the dynamics of urban invasions and informs future conservation efforts and urban planning in Brunei Darussalam. It contributes significantly to understanding and addressing the challenges of invasive plant species in rapidly developing urban environments.